Impact of Accounting Systems and Sharing Economy on Culinary MSMEs’ Financial Performance with Demographics Moderation - Luluq'il Jannah; Yuliusman Yuliusman; Salman Jumaili (International Forum of Researchers and Lecturers, 2025)
This research investigates how accounting information systems and sharing economy platforms affect the financial performance of culinary MSMEs in Jambi City, while also examining demographic factors as a moderating variable. The study involved Micro, Small, and Medium Enterprises (MSMEs) in the city’s culinary sector as both the population and sample. Using a non-probability purposive sampling method, data were gathered from 88 culinary MSME respondents through questionnaires and analyzed with the SmartPLS 4 software. The findings reveal that both accounting information systems and sharing economy platforms significantly impact the financial performance of culinary MSMEs. Furthermore, demographic factors were found to moderate the relationship between accounting information systems and financial performance, but did not moderate the link between sharing economy platforms and financial performance in the culinary MSME sector of Jambi City.